Approximate Controllability Results for Impulsive Partial Functional Nonlocal Integro-differential Evolution Systems through Resolvent Operators - Nagaraj, Mahalingam; Suganya, Selvaraj; Baleanu, Dumitru; Arjunan, Mani Mallika (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper investigates the existence and approximate controllability results for a class of impulsive functional integro-differential evolution systems with nonlocal conditions via resolvent operators in Banach spaces. By making utilization of Banach contraction principle and Schaefer’s fixed point theorem along with resolvent operators and semigroup theory, we build up the desired results. As an application, we also consider an impulsive partial functional integro-differential equations.